Elastisitas Harga dan Pendapatan Terhadap Permintaan Kredit Sepeda Motor di Kabupaten Manokwari - Yuyun Puji Rahayu (Perisai : Islamic Banking and Finance Journal, 2018)
The purpose of the research was to analyze the elasticity of credit of motorbike at PT. FIF in Manokwari Regency. The method used is descriptive statistical analysis method with interview and questionnaire instruments as guidelines. Data analysis was performed using a log-linear regression analysis tool to determine the elasticity of demand. The results showed that only the price had a negative and significant effect on the demand for motorcycle credit in Manokwari Regency. While the level of income does not affect the demand for motorcycle credit at 95% confidence level. The elasticity value of price demand is 0.079 <1, so its nature is inelastic. This means that the change in the price of credit goods is greater than the change in the number of motorcycle loans. Furthermore, the value of the elasticity of income shows that the motor credit is the income-inferior goods, where consumption of credit is inversely related to consumer income.